The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.euje.2006.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Use of strain and tissue velocity imaging for early detection of regional myocardial dysfunction in patients with beta thalassemia

Abstract: Thalassemia patients have regional systolic dysfunction in the lateral LV wall and regional diastolic dysfunction in the septal and RV wall. TVI and the newer modality SI are promising tools for quantitative assessment of regional myocardial function. SI seems more capable of early detection of regional myocardial dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
63
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 26 publications
12
63
0
Order By: Relevance
“…Tissue Doppler imaging can detect regional systolic and diastolic myocardial dysfunction earlier than global dysfunction in thalassemia patients [8][9][10][11][12][13]. Our results were in accordance with previous studies; [8].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Tissue Doppler imaging can detect regional systolic and diastolic myocardial dysfunction earlier than global dysfunction in thalassemia patients [8][9][10][11][12][13]. Our results were in accordance with previous studies; [8].…”
Section: Discussionsupporting
confidence: 95%
“…Therefore, T2* MR is still unsuitable for screening of patients with TM. Previous studies have reported that tissue Doppler imaging (TDI) can detect early myocardial dysfunction related to iron overload [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have elucidated the utility of strain rate imaging in the detection of myocardial diseases even in their subclinical stages, also as myocardial involvement in non-cardiac diseases, such as amyloidosis, diabetic heart disease, beta-thalassemia, Friedriech ataxia and others (74)(75)(76)(77)(78). It is also helpful in distinguishing between hypertrophic cardiomyopathy, athelete's heart and hypertrophy caused by hypertension (79,80).…”
Section: Figure 5 Normal Longitudinal Strain Pattern In the Color Dmentioning
confidence: 99%
“…Some reports indicate Doppler-echocardiogram with tissue Doppler as a promising technique for this situation [12][13][14][15][16][17][18][19] . However, data obtained by this method are still scarce, particularly in relation to left ventricular diastolic function and right ventricular structure and function.…”
mentioning
confidence: 99%